Local Administrative Organization and the Policy Responses to Climate Change: Policy Network Analysis - Senasu, Waranyoo; Piriyatanapat, Tachnawat (Thai Journal of East Asian Studies, 2019)
This article focuses on the policy responses of the local administrative organization to climate change. It emphasizes to explain the relationship between urban development and climate change response that is closely aligned with public policy issue. Regarding to Thailand’s climate change response, It has the passive nature of the policy framework. The role of a local administrative organization or city is unclear. However, there is an effort in respond to the problem. Meanwhile, national level has ‘the Master Plan’ which made it less connected to the local administration. In addition, state, and national mechanism does not have a unity, still play a variety of roles within state and local mechanisms. Organization, academic network and activist play a significant role in pushing the policy agenda. Thus, the duty of a local administrative organization responses to climate change is not only focus on ability to managing problem. However, to place great importance on network-policy management.